2011
DOI: 10.1111/j.1600-6143.2011.03551.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Bone Marrow-Based Immunosuppression Inhibits Rejection of Vascularized Composite Allografts in Nonhuman Primates

Abstract: Vascularized composite allograft (VCA) transplantation (also referred to as composite tissue allotransplantation) has demonstrated clinical success in cases of hand, arm and face transplantation despite prior belief that skin provides an insurmountable barrier to allograft rejection. These overall good outcomes are facilitated by substantial immunosuppressive requirements in otherwise healthy patients, yet still demonstrate frequent rejection episodes. We developed a nonhuman primate model of facial segment al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 29 publications
3
64
0
Order By: Relevance
“…It is also possible that the early management of rejection increases the long-term survival and outcomes of a skincontaining VCA. It has been reported that the bone marrow component of the VCA graft may confer immunogenic protection, and investigations including bone marrow infusions or bone marrow-derived mesenchymal stem cells have resulted in tolerance to VCA grafts, however, not without complications related to graft vs. host disease and post transplant lymphoproliferative disorders [40][41][42][43].…”
Section: Tissue Type Compositionmentioning
confidence: 99%
“…It is also possible that the early management of rejection increases the long-term survival and outcomes of a skincontaining VCA. It has been reported that the bone marrow component of the VCA graft may confer immunogenic protection, and investigations including bone marrow infusions or bone marrow-derived mesenchymal stem cells have resulted in tolerance to VCA grafts, however, not without complications related to graft vs. host disease and post transplant lymphoproliferative disorders [40][41][42][43].…”
Section: Tissue Type Compositionmentioning
confidence: 99%
“…Heterotopically transplanted facial segment VCA with vascularized BM treated only with tacrolimus and MMF but no radiation or T-cell depletion for induction demonstrated prolonged rejection-free survival, as compared with VCA without vascularized BM that experienced early rejection episodes and graft loss by postoperative day 7-15 [82]. While VCA with vascularized BM demonstrated sporadic low-level macrochimerism, acute and chronic rejection and graft loss occurred after discontinuation of maintenance immunosuppressive therapy.…”
Section: Minimizing Immunosuppression In Hand Transplantationmentioning
confidence: 98%
“…Along these lines, Barth et al developed a nonhuman VCA primate model utilizing selectively mismatched cynomolgus macaques of facial segment allotransplantation to elucidate the unique immunogenicity and immunosuppressive requirements of VCA with the addition of concomitant vascularized BM [82]. Heterotopically transplanted facial segment VCA with vascularized BM treated only with tacrolimus and MMF but no radiation or T-cell depletion for induction demonstrated prolonged rejection-free survival, as compared with VCA without vascularized BM that experienced early rejection episodes and graft loss by postoperative day 7-15 [82].…”
Section: Minimizing Immunosuppression In Hand Transplantationmentioning
confidence: 99%
“…Myriads of immunomodulatory protocols have been proposed for clinical applications based on our better understanding of immune mechanisms in VCA but they need to be validated in a large animal model that would be reasonably predictive of their performance in humans 7 . Based on physiologic and immunologic similarities between human and porcine organ systems 6 , swine VCA models can be considered reliable and cost-effective alternatives to canine 9 and nonhuman primate models 1 .…”
Section: Introductionmentioning
confidence: 99%